Utilization of information technology for elite athletes and coaches - Ito, K. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
The utilization of the sports-related information, e.g. movement evaluation, physiological measurements and training results, is vital to the success of elite athletes today. Many measurements and movie data are generated on a daily basis in sports training field. In addition, there are useful information resources to improve athletes' performance around the Internet. Strategically and efficiently uses of large amounts of information are essential for the competitive advancement. JISS provided the IT systems to sports federations in the London Olympics. In the paper, we present some general cases of utilizing information technology for elite sports.